The Role of Product Quality, Price, and Menu Variety in Enhancing Customer Satisfaction at a Local Café - Sa’adah, Silviana Khalilatus; Wibawa, Berto Mulia (Syntax Literate, 2025)
This study aims to determine whether there is an influence of product quality, price, and menu diversity on consumer satisfaction at Cafe REP Sidoarjo. In this study using independent variables, namely product quality (X1), price (X2), and menu diversity (X3) and dependent variables, namely menu diversity (Y). The population in this study is consumers who visit Cafe REP Sidoarjo. Determination of samples in this study using Accidental Sampling technique with a total sample of 120 respondents. Data collection techniques using questionnaires, after which they were analyzed using multiple linear regression analysis testing. From the results of the analysis conducted partially on the t test, it can be concluded that the product quality variable has a significant influence on consumer satisfaction at Cafe REP Sidoarjo. Price variables have a significant influence on consumer satisfaction at Cafe REP Sidoarjo. The variable of menu diversity has a significant influence on consumer satisfaction at Cafe REP Sidoarjo. In F-Test, it can be concluded that the three variables simultaneously affect customer satisfaction at Cafe REP Sidoarjo.